2021
DOI: 10.21037/atm-21-2158
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate ameliorates alcoholic fatty liver disease via reducing endotoxemia and inhibiting liver gasdermin D-mediated pyroptosis

Abstract: Background: Alcoholic fatty liver disease (AFLD) is characterized by hepatic steatosis and carries an elevated risk of cirrhosis and hepatocellular carcinoma. However, the mechanism of AFLD has not been elucidated thoroughly, and there are still no efficient therapies in clinic. Notably, butyrate, one kind of shortchain fatty acids produced by gut microbiota, has been shown to improve methionine-choline-deficient dietinduced non-alcoholic steatohepatitis. And our previous study found that butyrate ameliorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Previous studies have shown that butyrate can improve several models of liver injury, including nonalcoholic fatty liver (NAFLD) 24,39–41 and alcoholic fatty liver (ALD) 42 . Mechanistically, these effects are attributed to the ability to promote barrier function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that butyrate can improve several models of liver injury, including nonalcoholic fatty liver (NAFLD) 24,39–41 and alcoholic fatty liver (ALD) 42 . Mechanistically, these effects are attributed to the ability to promote barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that butyrate can improve several models of liver injury, including nonalcoholic fatty liver (NAFLD) 24,[39][40][41] and alcoholic fatty liver (ALD). 42 Mechanistically, these effects are attributed to the ability to promote barrier function. Our data suggest a novel mechanism by which butyrate alters susceptibility to ALI by activating the hepatic Nrf2 signalling pathway.…”
Section: Inhibition Of Nrf2 Counteracts the Protective Effect Of Buty...mentioning
confidence: 99%
“…As mentioned earlier, anti-inflammatory effects of BUT are well established (Cantu-Jungles et al 2019 ). Interestingly, BUT may also be of therapeutic potential in both alcoholic- and non-alcoholic fatty liver diseases (Ralli et al 2021 ; Zhang et al 2021 ). In addition, BUT has been advocated for treatment of obesity and sleep disorders (Baxter et al 2019 ; Szentirmai et al 2019 ) and most recently for control of cytokine storm associated with COVID-19 (Nithin et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that use of probiotic might be of potential use in prevention and treatment of alcohol-associated pathologies (Engen et al 2015 ; Lowe et al 2018 ; Rodriguez-Gonzalez and Orio 2020 ; Carbia et al 2021 ; Gupta et al 2021 ). In this regard, it was recently reported that butyrate (BUT) ameliorates alcoholic fatty liver disease in mice (Zhang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the treatment of AFLD mainly includes abstinence, nutritional support and drug therapy ( 6 ). The drug treatment mainly includes metadoxine, glucocorticoids, glycyrrhizic acid preparation and other drugs, which are not suitable for long-term use and are not specific drugs for AFLD ( 7 , 8 ). Therefore, the development of high-efficiency and low-toxicity therapeutic drugs for AFLD has become an urgent clinical need.…”
Section: Introductionmentioning
confidence: 99%